Effect of Financing to Deposit Ratio and Operational Efficiency on Profitability (ROA) with NPF as Intervening in Islamic Banks - Muhammad Tho'in (ITB AAS INDONESIA Surakarta, 2022)
The purpose of this research is to determine the effect of Financing to Deposit Ratio and Operational Efficiency on Profitability (ROA) with Non Performing Financing (NPF) as Intervening in Islamic Commercial Banks in Indonesia. This research method uses a quantitative descriptive approach. Research that allows statistical calculations to use numerical data, and is used as a data analysis tool by describing the data collected to finally reach a conclusion. The type of data used in this study is secondary data which is a monthly series of data with a time period of 2015-2021. The data used are financial ratio data provided by Statistics Indonesia Islamic Commercial Banks which include the ratio of Financing to Deposit Ratio (FDR), and Operational Efficiency, Return on Assets (ROA) and Non Performing Financing (NPF). Data collection techniques in this study by utilizing field studies. The variables used by the researcher are independent variables which include the ratio of FDR (X1) and Operating Expenses and Operating Income (X2), the dependent variable which includes the ratio of ROA and the intervening variable which includes the ratio of NPF. The data analysis method used in this research is multiple linear regression analysis and path analysis. Multiple linear regression analysis was conducted to determine the linear relationship between several independent variables (X) and the dependent variable (Y). While the path analysis method is a causality analysis that occurs when exogenous variables directly or indirectly affect endogenous variables. The results showed that partially the FDR and Operational Efficiency variables had an influence on the NPF variable. In addition, only and Operational Efficiency and NPF variables partially have an effect on ROA. Based on the results of the path analysis test, it can be explained that only the Operating Cost of Operating Income (X2) has an indirect effect on Return on Assets (Y) through NPF (Z). That is, the NPF variable is able to mediate the relationship between Operational Costs of Operating Income and Return on Assets.